An LC-MS/MS method for the simultaneous quantification of 32 steroids in human plasma - Šimková, Markéta; Kolátorová, Lucie; Drašar, Pavel; Vítků, Jana (Journal of chromatography. B, Analytical technologies in the biomedical and life sciences, 2022)
A development of robust and rapid method with simple sample preparation for the analysis of steroids of C18-, C19-, C21- families is of interest of many research groups. Here we present a novel LC-MS/MS method for the simultaneous quantification of 32 steroid hormones in human plasma. Twenty-two of them were analyzed directly without the need for derivatization, while ten were derivatized with 2-fluoro-1-methylpyridinium p-toluenesulfonate. The steroids were separated on a C18 column with a gradient elution consisting of methanol and water with the addition of 0.1% formic acid. The mass spectrometer was operated in positive ESI mode. Validation demonstrated that the method was applicable for the quantitative analysis of two C18- steroids (estrone, estradiol), nineteen C19- steroids (testosterone, epitestosterone, dihydrotestosterone, 11-ketodihydrotestosterone, 11β-hydroxyandrostenedione, 11β-hydroxytestosterone, 11-ketotestosterone, dehydroepiandrosterone, 7α-hydroxydehydroepiandrosterone, 7β-hydroxydehydroepiandrosterone, 7-ketodehydroepiandrosterone, androsterone, epiandrosterone, androstenedione, androstenediol, 5α-androstane-3α,17β-diol, 5α-androstane-3β,17β-diol, 5β-androstane-3α,17β-diol, 5β-androstane-3β,17β-diol), and eleven C21- steroids (cortisol, 21-deoxycortisol, 11-deoxycortisol, cortisone, corticosterone, 11-deoxycorticosterone, pregnenolone, 17-hydroxypregnenolone, progesterone, 17-hydroxyprogesterone, 5α-dihydroprogesterone). The lower limits of quantification are appropriate for analyses in both physiological and various pathophysiological conditions. The accuracy, intra- and inter-day precision values as well as stability tests were in accordance with FDA Guidelines. The method will be a useful tool in investigating the mechanisms of steroid-related diseases and will serve as a steppingstone for the development of other methods for steroid analyses in various biological matrices such as prostate tissue, cerebrospinal fluid, urine, seminal fluid, and saliva.
Keywords: Human plasma; Chromatography, Liquid; Humans; Tandem Mass Spectrometry; estron; androgeny; androstendion; Mass spectrometry; Androgens; lidé; tandemová hmotnostní spektrometrie; Estrone; chromatografie kapalinová; LC-MS/MS; Male; Liquid chromatography; Androstenedione; mužské pohlaví; Steroids